New data, same story: phylogenomics does not support Syrphoidea (Diptera: Syrphidae, Pipunculidae). (7th March 2018) - PAULI, THOMAS; BURT, TREVOR O.; MEUSEMANN, KAREN; BAYLESS, KEITH; DONATH, ALEXANDER; PODSIADLOWSKI, LARS; MAYER, CHRISTOPH; KOZLOV, ALEXEY; VASILIKOPOULOS, ALEXANDROS; LIU, SHANLIN; ZHOU, XIN; YEATES, DAVID; et al.
Abstract: The Syrphoidea (families Pipunculidae and Syrphidae) has been suggested to be the sister group of the Schizophora, the largest species radiation of true flies. A major challenge in dipterology is inferring the phylogenetic relationship between Syrphoidea and Schizophora in order to understand the evolutionary history of flies. Using newly sequenced transcriptomic data of Syrphidae, Pipunculidae and closely related lineages, we were able to fully resolve phylogenetic relationships of Syrphoidea using a supermatrix approach with more than 1 million amino acid positions derived from 3145 genes, including 19 taxa across nine families. Platypezoidea were inferred as a sister group to Eumuscomorpha, which was recovered monophyletic. While Syrphidae were also found to be monophyletic, the superfamily Syrphoidea was not recovered as a monophyletic group, as Pipunculidae were inferred as sister group to Schizophora. Within Syrphidae, the subfamily Microdontinae was resolved as sister group to the remaining taxa, Syrphinae and Pipizinae were placed as sister groups, and the monophyly of Eristalinae was not recovered. Although our results are consistent with previously established hypotheses on Eumuscomorphan evolution, our approach is new to dipteran phylogeny, using larger‐scale transcriptomic data for the first time for this insect group. Abstract : Nineteen de novo transcriptomes of nine dipteran families were analysed to test the monophyly of Syrphoidea (Syrphidae + Pipunculidae). The final data matrix comprised more than 1 million amino acid positions derived from 3145 genes, the largest dataset for Diptera so far. Pipunculidae was resolved as sister group to Schizophora, not grouped with Syrphidae. Within flower flies, the subfamily Eristalinae was recovered nonmonophyletic.